A Literary and Aesthetic Views of Mahmudhoja Behbudi (Eurasian Scientific Herald, 2022)
An important part of Behbudi's work is journalism. His work as a journalist, along with the organization of a bright side of the writer's talent, manifests itself as a passion of the people.The reason is that in each of his articles, he cares about our nation and its future.